Соціально-економічний механізм взаємодії ринків праці та освіти - Ільїч, Л.М. (Економіка промисловості, 2017)
Статтю присвячено проблемі гармонізації ринків праці та освіти. Запропоновано авторський підхід до побудови соціально-економічного механізму взаємодії ринків праці та освіти, який, на відміну від існуючих, базується на активізації соціального діалогу всіх зацікавлених сторін у збалансуванні попиту та пропозиції на кваліфіковану робочу силу і спрямований на забезпечення випереджувального розвитку та оновлення процесу підготовки (перепідготовки), підвищення кваліфікації кадрів відповідно до довгострокових планів соціально-економічного розвитку держави. Науково обґрунтовано доцільність функціонування механізму взаємодії ринків праці та освіти, який, базується на принципах системності, комплексності, достовірності, об’єктивності, конкретності, точності, комплексності та збалансованості, гнучкості й адаптивності, динамічності та варіативності, своєчасності, агломерації, безперервності та надійності, стратегічного спрямування, соціального партнерства, інноваційного характеру розвитку взаємодії, урахування інтересів усіх стейкхолдерів, правової захищеності, ділової етики. Статья посвящена проблеме гармонизации рынков труда и образования. Предложен авторский подход к построению социально-экономического механизма взаимодействия рынков труда и образования, который, в отличие от существующих, базируется на активизации социального диалога всех заинтересованных сторон в сбалансировании спроса и предложения на квалифицированную рабочую силу и направлен на обеспечение опережающего развития и обновление процесса подготовки (переподготовки), повышения квалификации кадров в соответствии с долгосрочными планами социально-экономического развития государства. Научно обоснована целесообразность функционирования социально-экономического механизма взаимодействия рынков труда и образования, который базируется на принципах системности, комплексности, достоверности, объективности, конкретности, точности, комплексности, сбалансированности, гибкости, адаптивности, динамичности, вариативности, своевременности, агломерации, непрерывности, надежности, социального партнерства, инновационного характера развития взаимодействия, учета интересов всех стейкхолдеров, правовой защищенности, деловой этики. The article is devoted to the problems of harmonization of labour and education markets. The author’s approach to the construction of socio-economic mechanism of interaction between labour and education markets is proposed based on the intensification of the social dialogue of all the parties concerned in balancing supply and demand for skilled labour by improving the national qualifications framework. The approach aims to provide proactive development and update process training (retraining), skills development according to long-term plans for socio-economic development of the state. Socio-economic mechanism of interaction between labour and education markets is a combination of interrelated social and economic relations actors of both markets aimed at optimizing the structure of occupational and qualification training according to economic requirements, balancing of labour supply and demand for achieving sustainable economic growth.Author scientifically substantiated the advisability of functioning of the socio-economic mechanism of interaction between labour and education markets, determined its organizational structure, goals, objectives, principles, forms and methods of cooperation between social partners, developed the directions of its improvement, and defined the methods of intensification of the social dialogue in the field of coordination of labour supply and demand. Socio-economic mechanism of interaction between labour and education markets is based on the principles of consistency, complexity, reliability, objectivity, concreteness, accuracy, comprehensiveness, balance, flexibility, adaptability, dynamism, variability, timeliness, agglomeration, continuity, reliability, strategic orientation, social partnership, the innovative character of cooperation, legal protection, business ethics etc. The paper presents a wide spectrum of cooperation forms for the main stakeholders and institutional instruments aimed at solving quantitative and qualitative mismatches in the labour market.